PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - saadah, lailatus; Permatasari, Annisa Indah; Muhammad Soedarman , Soedarman (Prodi Akuntansi FEB UNITOMO, 2024)
This research aims to determine the effect of profitability, leverage and company size on tax avoidance. This study uses a causal quantitative research with descriptive statistical analysis. The sampling technique uses purposive sampling was canducted on property and real estate companies listed on Indonesia Stock Exchange in 2021-2022 with a sample of 54 companies. The analysis method was processed using SPSS with data analysis techniques wich include normality test, multicolinearity test, heteroscedasticity test, autocorrelation test, coefficient of determination test (R²), and partial influence test (t test). The research results show that profitability and leverage influence tax avoidance. Meanwhile, company size has no effect on tax avoidance